PENGEMBANGAN MODEL PEMBELAJARAN GERAK DASAR LOKOMOTOR MELOMPAT UNTUK PENINGKATAN PERMAINAN LOMPAT KATAK SDN V 147 KAPASAN SURABAYA - Shardi Maulana Habibi; Bambang Ferianto Tjaahyo Kuntjoro (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The development of the physical education education and learning process for students of SDN V 147 Kapasan Surabaya, in carrying out the frog jump the educator or teacher teaches class II students to try in turns, so that the practical activities carried out are less efficient. The formulation of the problem in this research will define or give a describe how to improve a locomotor lower movement education model through the frog jumping game approach. The purpose of this research is to create educational procedures or sports learning models through playing fun frog jumping. The subject of this research was the teacher working with elementary school students at SDN V 147 Kapasan Surabaya as many as 28 students, of which there were 15 boys and 15 girls. The results of observations and diagnoses, learning methods show that learning basic locomotor movements, especially jumping movements, is still very monotonous and ineffective. In order for students to have good locomotor basic movement skills, fun learning methods are given in the form of games and are effective so that students are able to move optimally and reach a fitness level